Types of Attitudes toward Traits and Their Role in Selfand Other Assessments - Milena V. Baleva; Olga I. Polyanina; Irina V. Smirnova (Peoples' Friendship University of Russia (RUDN University), 2019)
The study integrates the experimental and descriptive approaches to the attitudes. The assumptions that the emotional, cognitive and behavioral components of attitudes toward personality traits, as well as the types of these attitudes mediate the selfand the Other assessments are under consideration. The study involved 314 students aged 18 to 30 years old (M = 20.23; SD = 1.59), of which 79 men (25%) and 235 women (75%). To measure attitudes toward traits, as well as the selfand the Other assessments, a list of 20 antonymic adjectives denoting personality characteristics was used. The objects of perception were young man and woman who answered the questions of the Short Dark Triad Questionnaire as an absolutely "good" or "bad" person. Using cluster analysis, diﬀerent types of attitudes toward traits were highlighted within each component (cognitive, emotional, and behavioral). These types were determined by the participants' position in relation to positive and negative traits. The attained results indicate that the subject's self-esteem depends on the attitudes toward traits and detects diﬀerent severity depending on the attitudes type. The highest self-esteem is observed in those subjects who: 1) consider that positive traits are more common than negative; 2) give highly contrast emotional ratings to positive and negative traits; 3) believe that positive traits are less controlled than negative ones. The assessment of the Other also reveals a connection with the types of the attitudes toward traits: the "good" Other is rated higher when the emotional attitudes toward traits are highly contrast, while the "bad" Other is rated higher when: 1) the negative traits are treated as more common; 2) the contrast between positive and negative traits is perceived as moderate. The results obtained open up the new perspectives for the correction of the selfand the Other assessments through the formation of attitudes toward traits.